The origin of the critically endangered Iberian lynx: Speciation, diet and adaptive changes. (1st September 2015) - Boscaini, Alberto; Madurell-Malapeira, Joan; Llenas, Manel; Martínez-Navarro, Bienvenido
Abstract: A new cranial fossil attributable to the species Lynx pardinus (Temminck, 1827) attests to the presence of this felid in the late Early Pleistocene of the Iberian Peninsula. Certain diagnostic features, such as the confluence of the lacerum posterius and anterior condyloid foramina, and the long and lyre-shaped temporal ridges, allow this find to be established as the first occurrence of the Iberian lynx in Europe. The fossil described here was found in the Avenc Marcel cave (Vallirana, Barcelona, Spain) in association with many other Late Villafranchian faunal remains. The combined presence of the bovid genera Capra and Soergelia, and the rodent species Mimomys medasensis and Mimomys tornensis, allows the age of this deposit to be placed at about 1.6–1.7 Ma. Consequently, the appearance of Lynx pardinus is related here to the faunal turnover that occurred between the Middle and Late Villafranchian, considered to be one of the major changes in the European macromammal fauna. Such an early divergence is in accordance with the evolutionary split proposed by both the molecular data and with the glacial-interglacial dynamics that affected the European region during the Early Pleistocene. Under these circumstances, the Iberian lynx could have originated in isolation in the Iberian Peninsula (a recognized southern European refugium for several species), during one or more glacial episodes. In this time period, this species may also have developed a dependence on small-sized animal prey, such as the lagomorphs of the genus Prolagus and Oryctolagus, already widespread throughout the Iberian Peninsula by that point. In the present work, several topics regarding the earliest evolutionary history of Lynx pardinus are discussed. Understanding the events that took place surrounding the origins of this lineage can shed new light on the future conservation of this extremely threatened felid. Highlights: We describe a new cranial remain ascribable to the species Lynx pardinus . The described neurocranium is, to date, the first occurrence of the taxon. The Iberian lynx diverged at the Middle-Late Villafranchian faunal turnover. Speciation can be the result of isolation during one or more glacial pulses. Fossils of Iberian lynxes show adaptation to feed upon small-sized prey.